AUTISMO Y SU INCIDENCIA EN EL DESARROLLO SOCIO-EMOCIONAL EN NIÑOS DE EDUCACIÓN INICIAL II - DELGADO ANCHUNDIA ADRIANA LILIBETH (2024)
Initial education in our country considers comprehensive care and diversity important in children under 5 years of age, therefore, addressing the issue of “Autism and its impact on the socio-emotional development in children in initial education II” is It is essential to identify that autism affects the child in adaptation, integration into the school and social environment, preventing the development of skills, abilities, interaction and learning in the educational process. This research work analyzed the impact of autism at this stage and how to treat it, in order to understand its impact on the socio-emotional development of children; It was carried out applying a mixed, non-experimental approach, using direct observation techniques with 25 children in the classroom, interviews with 2 teachers and surveys with 25 parents; With the data analyzed qualitatively and quantitatively, the results obtained allow us to know the characteristics of autism and how it manifests itself in children in the classroom, the impact on communication, social interactions and the development of abilities and skills, and the importance of support from parents in the evolutionary process of children. Concluding, the need to comprehensively address the issue of autism in early education is evident, to guarantee attention according to the condition and promote the socio-emotional development of children. The findings obtained serve as a basis for the teacher to implement strategies that lead to effective inclusion of students in initial education II of the Emigdio Esparza Moreno educational unit, in the city of Babahoyo.